# how do you sole this problem 7(b-6)=-12=b and11(2m+1)+12m=2+5(4=9m) also -(3-3p)+7(-2p-6)=-7p+9-10p-12making a note that i have analysis and functions not no other math so please help

### 3 Answers | Add Yours

Problem 1:

7b-42 = -12-b (I assume you meant -12-b not -12=b)

get all the b's on one side and the numbers on the other

8b = 30

b=30/8 or b = 3.75

Problem 2

First multiple where appropriate

22m +11+12m = 2 + 20 - 45 m (again assuming you meant 4-9m, not 4 = 9m)

simplify:

34m + 11 = 22 - 45m

get m's on one side, numbers on the other:

79m = 11

m = 11/79 or m =.1392

Problem 3 is done like #2

-3+3p-14p-42 = -7p + 9 - 10p - 12 simplify

-11p-45 = -17p-3

6p = 42

p = 7

If I was wrong about how I changed your equations, let me know and I'll redo.

Do you have too many "=" signs in the first two problems?

To solve the third one, first get rid of the brackets; you then have, after multiplying and dealing w/negative signs:

-3+3p-14p-42 = -7p+9-10p-12

Combine like terms on both sides of the equation (add numbers, and add terms containing "p"):

-45-11p = -17p-3

Get numbers on one side, terms containing "p" on the other (add 45 to each side, and add 17p to each side):

6p = 42

Divide each side by 6:

p = 7

While solving an equation, we add or subtract equal quantity to both sides of an equation, with an intention of making the variable or unkowns to one side and the known or numbers to the other side. Similarly we can multiply or divide by equal quantity on both sides of an equation (except zero, which no number or no quantity!).

i)

Given:7(b-6)=-12-b or

7b-42=-12-b .

Add 42+b to both sides to make unknown bon left and numbers on right.

7b-42**+42+b**=-12-b**+42-b** and now simplify both sides.

8b = 30. Divide by 8 both sides .

b=30/8=3.5

ii)

11(2m+1)+12m=2+5(4-9m)

22m+11+12m=2+20-45m

Add-11+45m to both sides to make m on left and numbers on right:

22m +11+12m **-11+45m **= 2+20-45m **-11+45m**

22m+12m+45m = 11

79m = 11. Divide both sides by 79 to get m:

m = 11/79

iii)

-(3-3p)+7(-2p-6)=-7p+9-10p-12.

-3+3p-14p-42 = -7p+9-10p-12

Collect the p's and number together on each side andsimplify:

-11p - 45 = -17p - 3.

Add 45+17p to both sides to male p's on one side and numbers on the other side:

-11p-45 **+45+17p** = -17p-3**+45+17p**

Simplify:

6p = 42. Divide both sides by 6 to get p

p = 7